PERFORMANS DEĞERLENDİRMEYE BİLİŞSEL YAKLAŞIM VE PSİKOMETRİK HATALAR. - BALTACI, Adem (Electronic Turkish Studies)
Performance appraisal, in the viewpoint of rater, is seen as a continuous process of information processing in order to make judgements about others. The cognitive approach that considers performance appraisal as a cognitive process, shows how raters make their judgements about performance and provides a better understanding for raters' cognitive structure and decision making process. Besides, this cognitive approach conceptualize the errors occurred from raters' human nature in the process of appraisal as “psychometric errors”. Ability to correctly understand, minimize aforementioned errors and improve effectiveness of appraisals can be achieved only by approaching the subject with cognitive perspective. Because of this approach that helps us to understand, explain and predict human nature in a better way, it is predicted that complexity of performance appraisals will be reduced, appraisal systems will be prepared more effectively and raters will be able to appraise more objectively and accurately. In this regard, the cognitive approach discussed in numerous studies in the international literature, started a strong trend as an interdisciplinary area of psychology and administrative sciences. However, it can be seen that in Turkish literature this interdisciplinary subject is overlooked and could not get the attention and emphasis it deserves, yet. In this theoretical study, it is presented that the cognitive information process of raters in performance appraisal is consisted of observation, categorization, storing, recalling, and decision making stages and this process is the source of psychometric errors. Also, the theoretical basis were stated for that the performance appraisal errors considered in the frame of system and rater errors in Turkish academic literature should be addressed with a new point of view as psychometric errors in oncoming studies.